Network Analysis of Osteoarthritis Progression Using a Steiner Minimal Tree Algorithm - Xie Y; Shao F; Ji Y; Feng D; Wang L; Huang Z; Wu S; Sun F; Jiang H; Miyamoto A; Wang H; Zhang C (Dove Medical Press, 2024)
Yujie Xie,1 Fanglin Shao,1 Yuxiu Ji,1 Dechao Feng,1,2 Ling Wang,3 Zonghai Huang,3 Shengjian Wu,1 Fuhua Sun,1 Hong Jiang,4 Akira Miyamoto,5 Haiming Wang,6 Chi Zhang1 1Rehabilitation Medicine Department, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People's Republic of China; 2Department of Urology, Institute of Urology, West China Hospital, Sichuan University, Chengdu, Sichuan, People's Republic of China; 3School of Information and Communication Engineering, University of Electronic Science and Technology, Chengdu, Sichuan, People's Republic of China; 4Rehabilitation Medicine Department, Xichong County People's hospital, Nanchong, Sichuan, People's Republic of China; 5Faculty of Rehabilitation, Nishikyushu University, Kansaitama, Japan; 6Department of Rehabilitation Medicine, the First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, People's Republic of ChinaCorrespondence: Haiming Wang, Department of Rehabilitation Medicine, the First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, People's Republic of China, Tel +868950771, Fax +86 830 8950771, Email wanghaiming866@163.com Chi Zhang, Rehabilitation Medicine Department, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People's Republic of China, Email chizhang_swmu@126.comPurpose: To provide a comprehensive analysis of associated genes with osteoarthritis (OA). Here, we reported a network analysis of OA progression by using a Steiner minimal tree algorithm.Methods: We collected the OA-related genes through screening the publications in MEDLINE. We performed functional analysis to analyze the associated biochemical pathways of the OA-related genes. Pathway crosstalk analysis was constructed to explore interactions of the enriched pathways. Steiner minimal tree algorithm was used to analyze molecular pathway networks. The average clustering coefficient was compared with the corresponding values of the Osteoarthritis-specific network. The new finding RNA was compared with former single-cell RNA-seq analysis results.Results: A gene set with 177 members reported to be significantly associated with Osteoarthritis was collected from 187 studies. Functional enrichment analysis revealed a specific related-OA gene including skeletal system development, cytokine-mediated signaling pathway, inflammatory response, cartilage development, and extracellular matrix organization. We performed a pathway crosstalk analysis among the 72 significantly enriched pathways. A total of 151 of the 177 genes in the Osteoarthritis gene set were included in the human interactome network. There were 31 genes in the former single-cell RNA-seq analysis results. The CLU, ENO1, SRRM1, UBC, HMGB1, NR3C1, NOTCH2NL, and CBX5 have significantly increased expression in seven molecularly defined populations of OA cartilage.Conclusion: The Steiner tree-based approach finds new biological molecules associated with OA genes.Keywords: network analysis, Steiner minimal tree, osteoarthritis, bioinformatics, osteoarthritis genes